Assessment of deep electrical conductivity features of Northern Victoria Land (Antarctica) under other geophysical constraints - ARMADILLO, EGIDIO; BOZZO, EMANUELE; FERRACCIOLI F.; CANEVA G.; CANEVA A. (Annals of Geophysics, 2000)
The lithospheric and crustal structure of the Victoria Land continental block (Antarctica) has been studied by geological and geophysical surveys. Among them magnetovariational investigations (MV) have been addressed to highlight the deep electrical conductivity patterns which contribute to the understanding of continental rifting and tectonic setting of the region. The hypothetical event map for H linearly polarized perpendicular to the coast indicates a possible broad coast parallel conductivity anomaly zone. Despite the coast effect, this feature could be related to the deep upper mantle thermal anomaly leading to Cenozoic uplift of the Transantarctic Mountains rift flank. However, both the hypothetic event map polarized parallel to the coast and the induction arrows suggest that the area of enhanced conductivity may be confined to the Deep Freeze Range crustal block along the western flank of the Mesozoic Rennick Graben. We also discuss the possible association between increased conductivity over the Southern Cross block and extensive Cenozoic alkaline plutonism.